Thermal, optical, structural, and electrical properties of ZnO-MoO3-TeO2 glasses - Ersundu, Miray Celikbilek; Ersundu, Ali Ercin; Bosak, Ondrej; Kubliha, Marian; Kostka, Petr (ELSEVIER SCI LTD, 2023)
A series of glasses in the ZnO-MoO3-TeO2 system were synthesized by conventional melt quenching technique. Thermal, optical, structural, and electrical properties of glasses were investigated according to the i) varying ZnO and MoO3 content at constant TeO2 and ii) substitution of TeO2 for ZnO + MoO3 in equimolar ratio. Substitution of glass former TeO2 for ZnO and/or MoO3 resulted in continuous structural transformation of TeO4 trigonal bipyramid units and to decomposition of tellurite network. The polaronic process is the major charge transport mechanism in these glasses, with charge transfer primarily occurring through the tellurite glass network. Evaluating the relationship between structural changes and electrical properties revealed that molybdenum oxide has a positive effect on electrical conductivity of glasses due to its weaker bonds. However, a free electron transport through the glass network is limited by Zn2+ ions. ZnO-MoO3-TeO2 glasses with their wide optical transmittance interval from 460 nm to 6.5 mu m, reaching above 70%, and the refractive index in the range of 1.96-2.15, and their relatively high electrical conductivity may find application in novel optoelectronic applications.
Keywords: Tellurite glass; MoO3; ZnO; Structural properties; Electrical conductivity; SYSTEM; NAPO3-MOO3; Materials Science